2022
DOI: 10.3389/fnut.2022.960228
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and osteogenic activity mechanism of casein phosphopeptide-calcium chelate

Abstract: Casein phosphopeptides (CPPs) are good at calcium-binding and intestinal calcium absorption, but there are few studies on the osteogenic activity of CPPs. In this study, the preparation of casein phosphopeptide calcium chelate (CPP-Ca) was optimized on the basis of previous studies, and its peptide-calcium chelating activity was characterized. Subsequently, the effects of CPP-Ca on the proliferation, differentiation, and mineralization of MC3T3-E1 cells were studied, and the differentiation mechanism of CPP-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The DHTEK−zinc complex formed more stable spherical particles with a particle size of 100−500 nm, which could dissociate and rechelate during gastrointestinal digestion, thus achieving the protection and transport of zinc ions. 102 Casein phosphopeptide, derived from milk proteins, could form stable NPs, which have also been reported to serve as delivery carriers for calcium, 103 zinc, 104 and iron. 105 To summarize, the potential usage of FPDMPs as effective delivery vehicles for minerals could not only guard the stability of metal ions by interacting with them but also modulate the self-assembly behavior of peptides and bestow new functions and properties to them, which hold immense potential for applications across diverse fields, including food science, biomedicine, and nanomaterials.…”
Section: Hydrogel Forming Ability Of Fpdmpmentioning
confidence: 99%
“…The DHTEK−zinc complex formed more stable spherical particles with a particle size of 100−500 nm, which could dissociate and rechelate during gastrointestinal digestion, thus achieving the protection and transport of zinc ions. 102 Casein phosphopeptide, derived from milk proteins, could form stable NPs, which have also been reported to serve as delivery carriers for calcium, 103 zinc, 104 and iron. 105 To summarize, the potential usage of FPDMPs as effective delivery vehicles for minerals could not only guard the stability of metal ions by interacting with them but also modulate the self-assembly behavior of peptides and bestow new functions and properties to them, which hold immense potential for applications across diverse fields, including food science, biomedicine, and nanomaterials.…”
Section: Hydrogel Forming Ability Of Fpdmpmentioning
confidence: 99%
“…When the organic ligand combines with the metal ion calcium, it causes the original absorption peak to shift or disappear or a new absorption peak to appear. 39 Therefore, the changes in the absorption wavelength and absorption intensity of the UV absorption spectrum are used to determine whether a new substance has been produced. Generally, the absorption peaks of peptide bonds in amino acid molecules are located between 200 and 300 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The findings were consistent with the previous studies. Wen Huang et al (2022) prepared CPP-calcium chelate and found it had positive effects on the proliferation and differentiation of MC3T3-E1 cells in vitro . Higher cell adhesion and proliferation and better cell adhesion morphology on PEEK-CPP samples might be relevant to the deeper valleys and grooves and higher hydrophilicity on PEEK-CPP surface.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some studies showed that CPP could facilitate the transcellular transport of Ca 2+ Li et al, 2021 found that CPP feeding substantially increased the femur index, serum Ca 2+ and serum osteocalcin levels, and femoral calcium content in rats. Moreover, in a study on the osteogenic ability of CPP-calcium chelate, it was proven that there were 321 differently expressed genes found in MC3T3-E1 cells and CPP might stimulate the osteogenic differentiation through AMPK signaling pathway, PI3K-Akt signaling pathway, MAPK signaling pathway, and Wnt signaling pathway, and the expression of NOTUM, WIF1, LRP4, APOD, OGN, and IGF1 (Huang et al, 2022).…”
Section: In Vitro Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation